ANALYSIS OF THE EFFECT OF ADVERTISING, SALES PROMOTION, AND PUBLIC RELATIONS ON SAVING DECISIONS AT PT. BANK NEGARA INDONESIA (PERSERO) Tbk. SURAKARTA OFFICE - Putra, Nadia; Samanto, Hadi; Utami, Wikan Budi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the influence of advertising, sales promotion, and public relations on customers’ saving decisions for BNI Taplus at PT Bank Negara Indonesia (Persero) Tbk. Surakarta Branch Office. The research method employed is a quantitative approach with a survey technique using questionnaires distributed to 100 respondents. The data were analyzed using multiple linear regression, classical assumption tests, as well as F-tests and t-tests. The results of the study indicate that simultaneously, advertising, sales promotion, and public relations have a significant effect on saving decisions. Partially, each of these variables also has a positive and significant influence. These findings demonstrate that integrated marketing communication activities play an important role in influencing customers' decisions in the banking sector. This research is expected to serve as a reference for bank management in formulating more effective marketing strategies in the future. Keywords: Advertising, Sales Promotion, Public Relations, Saving Decision